Clientelism in Venezuela’s Puntofijismo Period (1958 – 1988) - Torres, Sara (Tufts Archival Research Center, 2020)
This work brings forth an in-depth analysis of the role of clientelism in Venezuela’s transition to and consolidation of partyarchy (party rule). My thesis challenges the notion that Venezuela emerged as a model liberal or representative democracy following the 1958 Pact of Punto Fijo, introduces the factors that enabled and fostered clientelism at the local and institutional levels, and also in the informal and formal sectors. Unlike other scholars and authors who have written about the subject, I study Venezuela’s democratization through the lens of clientelism. This means, that unlike other scholars, who have looked at institutions, the role of oil, foreign investment, and also the historical and global context of democratization to explain Venezuela’s experience, I argue that those factors contributing to Venezuela’s democratization were, in reality, undergirded by the political parties’ instrumentalization of clientelism. Advisor: Professor Consuelo Cruz.